Serial 5-Year Evaluation of Side Branches Jailed by Bioresorbable Vascular Scaffolds Using 3-Dimensional Optical Coherence Tomography: Insights From the ABSORB Cohort B Trial (A Clinical Evaluation of the Bioabsorbable Everolimus Eluting Coronary Stent System in the Treatment of Patients With De Novo Native Coronary Artery Lesions). (September 2017) - Onuma, Yoshinobu; Grundeken, Maik J.; Nakatani, Shimpei; Asano, Taku; Sotomi, Yohei; Foin, Nicolas; Ng, Jaryl; Okamura, Takayuki; Wykrzykowska, Joanna J.; de Winter, Robbert J.; van Geuns, Robert-Jan; Koolen, Jacques; et al.
Abstract : Background—: The long-term fate of Absorb bioresorbable vascular scaffold (Abbott Vascular, Santa Clara, CA) struts jailing side branch ostia has not been clarified. We therefore evaluate serially (post-procedure and at 6 months, 1, 2, 3, and 5 years) the appearance and fate of jailed Absorb bioresorbable vascular scaffold struts. Methods and Results—: We performed 3-dimensional optical coherence tomographic analysis of the ABSORB Cohort B trial (A Clinical Evaluation of the Bioabsorbable Everolimus Eluting Coronary Stent System in the Treatment of Patients With De Novo Native Coronary Artery Lesions) up to 5 years using a novel, validated cut-plane analysis method. We included 29 patients with a total of 85 side branch ostia. From the 12 ostia which could be assessed in true serial fashion, 7 showed a pattern of initial decrease in the ostial area free from struts, followed by an increase in strut-free ostial area toward the end of the 5 years of follow-up. In a repeated-measures analysis with time as fixed variable and ostial area free from struts as dependent variable, we showed a numeric decrease in the estimated ostial area free from struts from 0.75 mm 2 (baseline) to 0.68 mm 2 (first follow-up visit at 6 months or 1 year) and 0.63 mm 2 (second follow-up visit at 2 or 3 years). However, from the second visit to the 5-year follow-up visit, there was a statistically significant increase from 0.63 to 0.89 mm 2 ( P =0.001). Struts overlying an ostium divided the ostium into compartments, and the number of these compartments decreased over time. Conclusions—: This study showed that in most cases, the side branch ostial area free from struts initially decreased. However, with full scaffold bioresorption, the ostial area free from scaffold increased between 2 to 3 years and 5 years in the vast majority of patients. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00856856. Abstract : Supplemental Digital Content is available in the text.